Shipping company strategies : global management under turbulent conditions - Lorange, Peter (Elsevier, 2005)
This book is about developing implementable strategies for shipping firms. It opens with an initial historical retrospective that highlights cases on A.P. Moller-Maersk and Leif Hoegh and Co. Here the reader is introduced to the global nature of competition in shipping, as well as the volatility of shipping markets. The book then turns to the question of how to play these markets. It looks at commodity based shipping company strategies for the bulk carrier, tanker container-ship and other segments. Here, the focus is on both going long-short, in-out, and maintaining a low cost base. Next is a.
Keywords: Shipping -- Management.; Merchant marine -- Management.; Strategic planning.; elektronické knihy; electronic books